Postmortem THC in decedents following legalization of recreational cannabis in Clark County, Nevada. Issue 4 (25th April 2022) - Neiswenter, Sean A.; Tupu, Momilani; Cross, Chad; Fudenberg, John; Harding, Brett E.
Abstract: Marijuana is the most prevalent illicit substance used globally. With increasing US legalizing recreational marijuana, more evidence is vital to minimize potential health risks. This study was conducted to test several hypotheses regarding postmortem THC/COOH‐THC in decedents before and after legalization of recreational marijuana in Nevada. We also compared presence of THC/COOH‐THC in decedents with respect to manner of death as recorded by the Clark County Office of the Coroner/Medical Examiner. THC/COOH‐THC concentrations for years 2015–2016 (pre‐legalization) and 2017–2019 (post‐legalization) were compared through an independent samples t ‐test and chi‐square tests. A binary logistic regression was used to compare the presence of THC/COOH‐THC with covariates: age, gender, race, and manner of death. The average concentration of THC/COOH‐THC detected per decedent did not significantly differ before and after recreational legalization, whereas the proportion of decedents testing positive for THC showed a small but significant increase following legalization although no significant change in COOH‐THC was detected. The likelihood of testing positive for THC/COOH‐THC decreased as age increased. Sex, race, and manner of death were all associated with the relative risk of presence of THC/COOH‐THC in toxicology reports. An increase in proportion of users but not in concentration of THC/COOH‐THC was observed after legalization. The results are generally consistent with national reports and suggest toxicology data from decedents is a valuable method for surveying marijuana use by the general public. The early adoption of recreational marijuana by neighboring states may have precluded any major changes in use following legalization in Nevada.